Delays during emergency obstetric care and their determinants among mothers who gave birth in South Gondar zone hospitals, Ethiopia. A cross-sectional study design - Gebrehiwot Ayalew Tiruneh; Mengstu Melkamu Asaye; Abayneh Aklilu Solomon; Dawit Tiruneh Arega (Taylor & Francis Group, 2021)
Background The majority of maternal deaths occur during delivery and the immediate postnatal period as a result of delays in seeking care, failure to reach health institutions, and receiving inappropriate health care. In developing countries, delayed access to timely healthcare contributes to high maternal mortality and morbidity. Objective This study aimed to assess the delays during emergency obstetric care and associated factors with delays during emergency obstetric care. Method A cross-sectional study design was conducted. We chose five hospitals at random in the South Gondar zone, Ethiopia. Face-to-face Interviews were conducted with 459 participants using a systematic sampling technique. For this analysis, bi-variable and multivariable logistic regression models were used. The Adjusted Odds Ratio was used to determine the statistical association with delays during emergency obstetric care at p-value <0.05 with a 95% confidence interval. Results The proportion of delays during emergency obstetric care were found to be 59.7% in this study. The respondents' mean age was 27.23 years old, with a standard error of 5.67. Pregnant mothers living in the rural areas (AOR: 4.1, 95%, CI: 2.36 to 6.25), no ANC visit (AOR: 1.8, 95% CI: 1.32 to 3.18), uneducated women (AOR: 4.6, 95% CI: 2.45 to 8.59) and referral to a higher level of care (AOR: 2.7, 95% CI: 1.60 to 4.44), were all significantly associated with delay. Conclusion Delay during emergency obstetric care was found to be 59.7 percent. Rural residency, absence of ANC visit, uneducated mothers, and referred mothers from one level to the next level of care were factors that contributed to delays in emergency obstetric care in the study area.